Progression of Friedreich ataxia: quantitative characterization over 5 years. Issue 9 (25th July 2016) - Patel, Maya; Isaacs, Charles J.; Seyer, Lauren; Brigatti, Karlla; Gelbard, Sarah; Strawser, Cassandra; Foerster, Debbie; Shinnick, Julianna; Schadt, Kimberly; Yiu, Eppie M.; Delatycki, Martin B.; Perlman, Susan; et al.
Abstract: Objective: Friedreich ataxia (FRDA) is a progressive neurodegenerative disorder of adults and children. This study analyzed neurological outcomes and changes to identify predictors of progression and generate power calculations for clinical trials. Methods: Eight hundred and twelve subjects in a natural history study were evaluated annually across 12 sites using the Friedreich Ataxia Rating Scale (FARS), 9‐Hole Peg Test, Timed 25‐Foot Walk, visual acuity tests, self‐reported surveys and disability scales. Cross‐sectional outcomes were assessed from recent visits, and longitudinal changes were gaged over 5 years from baseline. Results: Cross‐sectional outcomes correlated with measures of disease severity. Age, genetic severity (guanine‐adenine‐adenine [GAA] repeat length), and testing site predicted performance. Serial progression was relatively linear using FARS and composite measures of performance, while individual performance outcomes were nonlinear over time. Age strongly predicted change from baseline until removing the effects of baseline FARS scores, when GAA becomes a more important factor. Progression is fastest in younger subjects and subjects with longer GAA repeats. Improved coefficients of variation show that progression results are more reproducible over longer assessment durations. Interpretation: While age predicted progression speed in simple analyses and may provide an effective way to stratify cohorts, separating the effects of age and genetic severity is difficult. Controlling for baseline severity, GAA is the major determinant of progression rate in FRDA. Clinical trials will benefit from enrollment of younger subjects, and sample size requirements will shrink with longer assessment periods. These findings should prove useful in devising gene therapy trials in the near future.